2019
DOI: 10.3390/ijms20051207
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Diversity of Spitsbergen Soil Microbial Communities Suggests Their Potential as Plant Growth-Promoting Bacteria

Abstract: The objective of the study was to assess the physiological diversity and metabolic activity of the soil bacterial communities inhabiting Spitsbergen soils in search of bacterial abilities facilitating plant growth promotion. In the soil, the total number of culturable microorganisms, the number of their individual physiological groups (including Siderophore Synthesizing; SSB and Phosphate Solubilizing Bacteria; PSB), the dehydrogenase (DH) activity, and the ability to utilize sources of C, N, P (EcoPlate) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 76 publications
0
14
0
1
Order By: Relevance
“…In our previous studies [35], the S17 isolate was biochemically identified as Gram-negative (Figure 1A) Pseudomonas luteola , and characterized by growth on oligotrophic and coptotrophic media, the activity of ACC (1-aminocyclopropane-1-carboxylate) deaminase, the concentration of IAA, and the Minimal Inhibitory Concentration (MIC) for Cu. We also obtained positive results in the following tests: the activity of protease, β-glucosidase, and β-galactosidase; the reduction of nitrate to nitrite ions; the fermentation of d -glucose, the hydrolysis of d -glucose, l -arabinose, d -mannose, d -mannitol, N -acetylglucosamine, d -maltose, gluconate, malate, and citrate; phosphate solubilization on Pikovskaya (PVK) medium (Figure 1B); and the production of siderophores on blue agar with chrome azurol S medium (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous studies [35], the S17 isolate was biochemically identified as Gram-negative (Figure 1A) Pseudomonas luteola , and characterized by growth on oligotrophic and coptotrophic media, the activity of ACC (1-aminocyclopropane-1-carboxylate) deaminase, the concentration of IAA, and the Minimal Inhibitory Concentration (MIC) for Cu. We also obtained positive results in the following tests: the activity of protease, β-glucosidase, and β-galactosidase; the reduction of nitrate to nitrite ions; the fermentation of d -glucose, the hydrolysis of d -glucose, l -arabinose, d -mannose, d -mannitol, N -acetylglucosamine, d -maltose, gluconate, malate, and citrate; phosphate solubilization on Pikovskaya (PVK) medium (Figure 1B); and the production of siderophores on blue agar with chrome azurol S medium (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study [35], the S17 isolate was biochemically identified using API 20 NE V8.0 tests, and was characterized by ACC (1-aminocyclopropane-1-carboxylate) deaminase activity, MIC for Cu, and the ability to synthesize IAA and produce siderophores (on the chrome azurol S agar medium). A germination test of Phaseolus coccineus plants inoculated with the S17 isolate was carried out as well [35].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations